Analisa Susunan Terminal Udara Sistem Proteksi Petir Menggunakan Metode EGM Eriksson Pada Bangunan PT. TELKOM Pekanbaru - Rizky Johari; Edy Ervianto; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Pekanbaru city is a city located in an area that has a large enough lightning density level that is equal to 136 days per year with a density of lightning strikes to the ground (Ng) reached19,5128 strikes/ km2/ year. So it can endanger the high buildings as being in PT. TELKOM Pekanbaru. PT. TELKOM Pekanbaru is the central distribution of data throughout the RiauMainland telecommunication, where it needs a reliable protection system. The aim of this study is to introduce a new method introduced in the IEEE publication, IEEE 998TM-2012, on the lightning protection called EGM Eriksson method. This study uses a Eriksson EGM method to analyze the composition of the air terminal building PT. TELKOM Pekanbaru, which will then determine the area of protection of the external lightning protection system All of this analysis is described in three dimensions using Sketchup 2015 and showed good protection results.Keywords : lightning protection, EGM, Eriksson